L'Hôpital's rule

  • #1

Homework Statement



Find the limit as x->0+ of (ln(x))^x

*The answer is 1*


Homework Equations



l'Hôpital's rule



The Attempt at a Solution



lim (ln(x))^x = 0^0

I took the ln of that quantity to bring down the x

lim = x*ln(ln(x))

lim = ln(ln(x)) / (1/x)

Then I used l'Hôpital's rule

1/(x*ln(x)/(1/x^2)

= 1/(x^3*ln(x))

I got stuck here. If I plug in zero I get 0^3 and a undefined answer in the denominator. Do I have to do l'Hôpital's rule on the bottom again?
 
Last edited:

Answers and Replies

  • #2
35,284
7,124
It seems that you edited this problem while I was composing an answer. The first problem I saw was lim (-ln(x))^x, as x approached 0+.
A little while later, the minus sign in front of ln(x) was gone. Here's my work for the original problem. For the edited problem, no limit exists.

[tex]Let y = (-ln x)^x[/tex]
[tex]ln y = x ln(-ln(x)) = \frac{ln(-ln(x))}{\frac{1}{x}}[/tex]

[tex]lim_{x \rightarrow 0^+} ln y = lim_{x \rightarrow 0^+} \frac{ln(-ln(x))}{\frac{1}{x}} [\frac{\infty}{\infty}][/tex]

[tex]= lim_{x \rightarrow 0^+} \frac{\frac{1}{-ln(x)}\frac{-1}{x}}{\frac{-1}{x^2}} [/tex]
[tex]= lim_{x \rightarrow 0^+} \frac{-x}{ln(x)} = 0[/tex]
Since [tex]lim_{x \rightarrow 0^+} ln y = 0[/tex]
Then [tex]ln(lim_{x \rightarrow 0^+} y) = 0[/tex]
Or [tex]lim_{x \rightarrow 0^+} (-ln(x))^x = 1[/tex]
 

Related Threads on L'Hôpital's rule

  • Last Post
Replies
4
Views
5K
  • Last Post
Replies
1
Views
865
  • Last Post
Replies
13
Views
2K
  • Last Post
Replies
8
Views
6K
  • Last Post
Replies
9
Views
2K
  • Last Post
Replies
12
Views
4K
  • Last Post
Replies
9
Views
4K
  • Last Post
Replies
1
Views
2K
  • Last Post
Replies
2
Views
939
  • Last Post
Replies
4
Views
1K
Top